Modulation of human mesenchymal stem cell survival on electrospun mesh with co-immobilized epithelial growth factor and gelatin. Issue 69 (29th July 2015) - Shin, Young Min; Lim, Jong-Young; Park, Jong-Seok; Gwon, Hui-Jeong; Jeong, Sung In; Ahn, Sung-Jun; Shin, Heungsoo; Lim, Youn-Mook
<x xml:space="preserve">Abstract</x> Co-immobilization of EGF and gelatin on a fibrous mesh promotes spreading and viability of hMSC, and coupled EGF involves involucrin expression and procollagen secretion, indicating trans-differentiation to keratinocyte-like cell.